Predicted substantiated silent discourse reading (P.S.S.D.R.) - Labrador, Vilma (1991)
PSSDR is an instructional reading strategy consistent with a thinking-language view of reading. The extent and subtitles of its variations make it one of the major teaching strategies for use in learning to read as well as in reading to learn.
Keywords: Reading strategies